STRATEGI PEMASARAN BUAH SEMANGKA BULAT NON BIJI TERHADAP PENDAPATAN PETANI DI DESA TRIYOSO KECAMATAN BELITANG KABUPATEN OKU TIMUR - Aminullah (Jurnal Bakti Agribisnis, 2015)
The purpose of this research were to : (1) To know the income of non-seedled watermelon farm in Triyoso Village, Belitang Sub-district, OKU Timur Regency, (2) To know the marketing strategy of non-seed watermelon farming in Triyoso Village Belitang District, OKU Timur Regency through descriptive analysis of SWOT . This research was conducted in Triyoso Village, Belitang District, East OKU Regency. The location of the study was determined purposively (Purposive) with the consideration that this area is a potential watermelon producer and plays an important role for the availability of watermelons in Triyoso and Belitang District. The research has been conducted in march 2014 to complete. The study found that the average non-grade A grade seed yield was 13,819, the class B average production was 2,210 kg / production process, and the C class was 558 kg with the total production amount of 16,587 and the average yield of the non- The average production cost of Rp 17,502,344 / production process obtained an average non-kernel round watermelon income of Rp 43,035,720 / production process and Strategy that can be developed in Marketing of non-seed round watermelon fruit in Triyoso Village Belitang District are: Maintaining the quality of seed products and enhancing cooperation with stakeholders and strengthening partnerships to maintain continuity of production and can survive in the market, monitoring the marketing risk of watermelon fruit with the government, Improving the management of watermelon farming Round non seed through cooperation With relevant agencies in order to increase competitiveness in the marketing of watermelon fruit.